Penggunaan Media Kartu Dalam Hafalan Surah-Surah Pendek Di TK/TPA Aqidah Palangka Raya - Rusma Hidayati; Hadma Yuliani; Luvia Ranggi Nastiti (Pakis Journal Institute, 2024)
This service was carried out to introduce and use card media to remember the extent of memorization of short surahs of santriwan and santriwati in TK/TPA Aqidah Palangka Raya. And also with the use of this card media helps santriwan and santriwati in memorizing short surahs. Community service carried out directly by researchers at one of the Islamic religious education institutions, namely TK / TPA Aqidah Palangka Raya. With the existence of this card media can help children in remembering something that has been memorized before such as memorizing short surahs. The use of card media and this game, children will be honed in their ability to remember and be active in the classroom so that memorization that has been memorized continues to be remembered and memorization of these surahs can also be read when performing prayer services.